Tesla's attic - Shusterman, Neal 1962-; Elfman, Eric 1958- (Disney Hyperion Books, 2014)
"With a plot combining science and the supernatural, four kids are caught up in a dangerous plan concocted by the eccentric inventor, Nikola Tesla"...
Keywords: Tesla, Nikola; Inventions; Science fiction; Colorado Springs (Colo.); Jugendbuch